Ekstraksi Sederhana Antosianon dari Kulit Buah Naga (Hylocereus polyrhizus) sebagai Pewarna Alami - Sri Sudarmi; Purwo Subagyo; Anna Susanti; Anggun Sri Wahyuningsih (Eksergi, 2015)
Natural dyes can be obtained from the pigments that contained from leaves, fruit, and rind of the plants. Dragon fruit peel is one of the potential  natural pigment source. Almost 30-35% of the peel fruit is often simply thrown away as trash. Dragon fruit peel  provides natural red color produced by pigment called anthocyanin which can be used as a subtituent from synthetic dyes to natural dyes. This research was objected to find the optimum conditions for anthocyanin extraction of dragon fruit peel. Simple extraction was carried out by using 80% ethanol solvent with  variable ratio of the amount of material and solvent (1: 9 to 1:13), temperature (50◦ to 80◦ C) and time (1 to 5 hours). Optimum result was obtained from a ratio F: S 1:11, temperature 50◦C, for 3 hours.